A review of agility: Practical applications for strength and conditioning - Young, W.; Farrow, D. (Strength and Conditioning Journal, 2006)
Agility is an important component of many sports but has not been extensively researched. The various components that contribute to agility performance are discussed and training guidelines are provided. There appears to be limited transfer to agility performance from straight sprint training as well as from general strength training. The principle of training specificity is emphasized to achieve maximum transfer to onfield performance.